Equality Deferred:: The Origins of the Newfoundland Human Rights State - Clemént, Dominique (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2012)
Canada has constructed the most sophisticated human rights legal regime in the world, and yet local conditions have determined the emergence and implementation of human rights law. Newfoundland is an ideal case study. The government’s lackluster support for human rights policy demonstrates how governments can inhibit the application of law. In addition, the predominance of sex discrimination complaints offers a unique insight into the dynamics of gender inequality during this period. Finally, this case study demonstrates the critical role that social movements have played in implementing human rights law in Canada, which has historically depended on the participation of non-state actors.